Effect of different cooling rate on integrated circuit (ic) package - Amir Syahmi, Nordin (2013)
Currently, electronic products have shrunk into smaller size and in order to increase the input/output (I/O) counts as well as to improve performance. The goal of this study is to determine the reliability and strength of the solder joint formed at the integrated circuit (IC) interconnection with the board. The strength of the joint is based on the intermetallic compound (IMC) formation at the joint. Free lead based solders have been used nowadays due to the environmental and health hazard effect of the lead based solder. Two types of surface finish have been used in this study which was electroless/nickel immersion gold (ENIG) and bare copper substrate as the reference in the research. All specimens will be subjected to reflow soldering with slow and fast cooling rate apply on the sample. Then, all specimens will undergo isothermal ageing at 150°C for 250 hour and 500 hour. The IMC formed at the solder joints of all specimens were studied in terms of thickness and cooling rate applied on it. Characterization on the specimen is done by the cross section of the joint to see the IMC formation on the solder joint. It can be concluded that, the fast cooling rate forms large IMC compared to slow cooling rate which is much thinner than fast cooling rate. Besides that, it was found that IMCs thicknesses are proportional with ageing durations. However, thicker IMC was found on the bare copper substrate joint compare to ENIG surface joint after ageing treatment, indicating higher growth rate of IMCs formed at the bare cooper substrate